Status of the sunken nuclear submarine Komsomolets in the Norwegian Sea - Justin P. Gwynn; Hilde Elise Heldal; Hans-Christian Teien; Andrey Volynkin; Simon M. Jerome; Ole Christian Lind (Proceedings of the National Academy of Sciences, 2026)
The study documents in detail the extent of damage to the exterior of the sunken nuclear submarine Komsomolets and that previous remedial action carried out by Russia was still in place. No evidence was found of any plutonium in the near environment around the damaged forward section of the submarine from the nuclear warheads that were reported to be part of Komsomolets armament in the torpedo compartment. It was confirmed that releases from the reactor were still occurring, but not continuously, with maximum activity concentrations of 90 Sr and 137 Cs that were 400,000 and 800,000 times higher, respectively, than typical levels of these radionuclides in the Norwegian Sea. Elevated levels of 239 Pu, 240 Pu, and 236 U were also detected in the releases from the reactor, with atom ratios of 240 Pu/ 239 Pu and 236 U/ 239 Pu that indicate that the nuclear fuel in the reactor is corroding. Despite that releases from the reactor have occurred for over 30 y, there is little evidence of any accumulation of radionuclides in the near environment around the submarine as the released radionuclides appear to be rapidly diluted in the surrounding seawater. Releases from the reactor in Komsomolets can be expected to continue, so further investigations should be carried out to determine the mechanisms behind the observed releases, the corrosion processes that are occurring within the reactor and the implications of these for further releases and the fate of the remaining nuclear material in the reactor.